2019
DOI: 10.1016/j.fuel.2018.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline flame behavior at elevated temperature and pressure

Abstract: Freely propagating laminar premixed flames of stoichiometric mixtures of gasoline surrogate and iso-octane with air are computed using three chemical kinetics mechanisms of varied complexity and detail. A good agreement of the computed burning velocities with past experimental data is observed. The burning velocities of these mixtures at temperature of 850 ≤ T ≤ 950 decrease with pressure up to about 3 MPa and starts to increase beyond this pressure. This contrasting behavior is related to the role of pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The most dangerous δ values in various confined spaces were slightly different because of different experimental ambient conditions, but were all concentrated at about 1.70% [1,33,34]. In order to study gasoline−air mixture explosion overpressure characteristics and flame propagation behaviors more accurately, the experiments adjusted δ in the range of 1.40−2.00%, including from lean−burn conditions (δ = 1.40%, 1.50%) to suitable−burn conditions (δ = 1.60%, 1.70%, 1.80%) and then to rich−burn conditions (δ = 1.90%, 2.00%).…”
Section: Experimental Schemementioning
confidence: 97%
See 1 more Smart Citation
“…The most dangerous δ values in various confined spaces were slightly different because of different experimental ambient conditions, but were all concentrated at about 1.70% [1,33,34]. In order to study gasoline−air mixture explosion overpressure characteristics and flame propagation behaviors more accurately, the experiments adjusted δ in the range of 1.40−2.00%, including from lean−burn conditions (δ = 1.40%, 1.50%) to suitable−burn conditions (δ = 1.60%, 1.70%, 1.80%) and then to rich−burn conditions (δ = 1.90%, 2.00%).…”
Section: Experimental Schemementioning
confidence: 97%
“…The overpressure changing trend, which showed the development law of first increasing and then decreasing as time goes on, was basically the same in different conditions, and demonstrated one obvious overpressure peak (p max ). Li [1], Ghiasi [33] and Mitu et al [34] found that the formation of p max is related to the combustion reaction speed and explosion releasing speed in the gasoline-air mixture explosion process. p max changed significantly at different δ.…”
Section: Explosion Overpressure Development Processmentioning
confidence: 99%
“…The Vibe function has many calculation variants [3,35,36] taking into account at least a few parameters, but despite everything, its characteristic shape seems to undergo only a specific stretching or narrowing along the axis of the argument, the crank angle (ca). However, because it was necessary to provide specific parameters of this function, for example, to create graphic illustrations in the further part of the analysis, the influence of several most important parameters necessary to determine the Vibe function was taken into account, which included the following values:…”
Section: Enginesmentioning
confidence: 99%
“…Emission regulations for car engines are becoming more stringent to reduce the environmental impact of fossil fuel combustion in engines. This has forced humans to find new energy and new combustion technologies to provide cleaner, more efficient, heat-efficient combustion with extremely low emissions of NOx, soot, and other pollutants. High-density gasoline fuel surrogate is a good research object. Gasoline is one of the high-density hydrocarbon fuels with very complex components, so it is difficult to study the combustion process.…”
Section: Introductionmentioning
confidence: 99%